Hyperoxia-induced lung structure–function relation, vessel rarefaction, and cardiac hypertrophy in an infant rat model - Francesco Greco; Susanne Wiegert; Philipp Baumann; Sven Wellmann; Giovanni Pellegrini; Vincenzo Cannizzaro (Journal of Translational Medicine, 2019)
Abstract Background Hyperoxia-induced bronchopulmonary dysplasia (BPD) models are essential for better understanding and impacting on long-term pulmonary, cardiovascular, and neurological sequelae of this chronic disease. Only few experimental studies have systematically compared structural alterations with lung function measurements. Methods In three separate and consecutive series, Sprague–Dawley infant rats were exposed from day of life (DOL) 1 to 19 to either room air (0.21; controls) or to fractions of inspired oxygen (FiO2) of 0.6, 0.8, and 1.0. Our primary outcome parameters were histopathologic analyses of heart, lungs, and respiratory system mechanics, assessed via image analysis tools and the forced oscillation technique, respectively. Results Exposure to FiO2 of 0.8 and 1.0 resulted in significantly lower body weights and elevated coefficients of lung tissue damping (G) and elastance (H) when compared with controls. Hysteresivity (η) was lower due to a more pronounced increase of H when compared with G. A positive structure–function relation was demonstrated between H and the lung parenchymal content of α-smooth muscle actin (α-SMA) under hyperoxic conditions. Moreover, histology and morphometric analyses revealed alveolar simplification, fewer pulmonary arterioles, increased α-SMA content in pulmonary vessels, and right heart hypertrophy following hyperoxia. Also, in comparison to controls, hyperoxia resulted in significantly lower plasma levels of vascular endothelial growth factor (VEGF). Lastly, rats in hyperoxia showed hyperactive and a more explorative behaviour. Conclusions Our in vivo infant rat model mimics clinical key features of BPD. To the best of our knowledge, this is the first BPD rat model demonstrating an association between lung structure and function. Moreover, we provide additional evidence that infant rats subjected to hyperoxia develop rarefaction of pulmonary vessels, augmented vascular α-SMA, and adaptive cardiac hypertrophy. Thus, our model provides a clinically relevant tool to further investigate diseases related to O2 toxicity and to evaluate novel pharmacological treatment strategies.